1984
DOI: 10.1177/0148607184008005542
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Selenium Status in Home Parenteral Nutrition Patients with Small Bowel Resections

Abstract: The selenium status of 13 adult home parenteral nutrition (HPN) patients was evaluated using 12 healthy adult volunteers as controls. Patients had been maintained on HPN for a mean of 36 months and averaged 121 cm of residual small bowel. Prospective diet surveys in patients indicated a mean oral caloric intake of 902 kcal/day. The mean plasma selenium concentrations (microgram/g) were 0.044 in patients and 0.117 in controls (p less than 0.01). The erythrocyte glutathione peroxidase activities, as mumol of NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A lower glutathione peroxidase activity, indicative of the low cellular selenium status, was associated with muscle pain and weakness. In these cases, the affected patients responded favorably to selenium administration [ 24 ]. The effects of selenium administration were also tested in patients featuring myotonic dystrophies, since it was observed that their selenium level in blood decreased with the evolution of the disease [ 25 ].…”
Section: The Importance Of Selenium In Muscle Physiologymentioning
confidence: 99%
“…A lower glutathione peroxidase activity, indicative of the low cellular selenium status, was associated with muscle pain and weakness. In these cases, the affected patients responded favorably to selenium administration [ 24 ]. The effects of selenium administration were also tested in patients featuring myotonic dystrophies, since it was observed that their selenium level in blood decreased with the evolution of the disease [ 25 ].…”
Section: The Importance Of Selenium In Muscle Physiologymentioning
confidence: 99%
“…A relation between selenium deprivation and muscle pain or weakness was initially described in patients under prolonged parenteral nutrition (Brown et al 1986;Kelly et al 1988;van Rij et al 1979;Baptista et al 1984). The characteristic features in the myocardial muscle of these patients are reminiscent of Keshan disease.…”
Section: Selenium-related Muscle Disorders In Human and Livestockmentioning
confidence: 99%
“…Low plasma Se concentrations and lower erythrocyte Gpx activities were associated with muscle pain and weakness. Accordingly, affected patients responded positively to Se administration [36]. The benefits of Se administration were also tested in patients with myotonic dystrophies, since it was observed that their Se levels in blood decreased with the evolution of the disease [37].…”
Section: Muscular Dysfunction Associated With Selenium Deficiencies I...mentioning
confidence: 99%